2023
DOI: 10.1186/s12909-023-04307-z
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of health care professionals towards interprofessional teamwork in Ashanti Region, Ghana

Abstract: Background Interprofessional collaboration ensures that high-quality health care is provided leading to improved health outcomes and provider satisfaction. Assessing the attitudes of health care professionals towards teamwork in Ghana is novel. Objective To examine the attitudes of health care professionals towards interprofessional teamwork and assess specific attributes influencing these attitudes in the Ashanti region, prior to implementing an i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…As the demand for ICU nurses is increasing, especially during the COVID-19 period [11], an increasing number of new nurses are joining this group. Edward suggested that the teamwork attitudes of young nurses in the ICU were lower than those of nurses over 35 years old [12]. It was also shown by O'connor that junior nurses had poor teamwork [13].…”
Section: Introductionmentioning
confidence: 99%
“…As the demand for ICU nurses is increasing, especially during the COVID-19 period [11], an increasing number of new nurses are joining this group. Edward suggested that the teamwork attitudes of young nurses in the ICU were lower than those of nurses over 35 years old [12]. It was also shown by O'connor that junior nurses had poor teamwork [13].…”
Section: Introductionmentioning
confidence: 99%